A of Political-Social Discourse Analysis of the Relationship between Lover and Beloved onein the lyric poems of Sa’di - Alli Akbar Bagheri Khalili; monireh Mehrabi Kalli (متن شناسی ادب فارسی, 2017)
In romantic literature of Iraqi style, particularly in Sa’di’s lyric poems, the cruelty and oppression of the sweetheart and the degradation and contempt of the lover in front of her are proposed abundantly. Despite the holiness which the love has in Persian literature,it is sometimes thought of as an obstacle on the way of lover. The research question is: are concepts and aims beyond the worldly love? To answer this question, one-fourth of Sa’di’s lyric poems were examined based on the analysis of political-social dispute. The result of the research represented that with such content-makings, the poet is the representative of the nation. He protests loudly against the cruelty and oppression of the beloved person who can bethe symbol of despotic and autocratic kings. The metaphor of "love is obstacle" indicates the conflict of lover-beloved one’s dispute. The metaphor of "love is trap" shows that the sweetheart attempts to dominate the lover thoroughly. This image conforms to lord and former, or shepherd and herd idea between governors and inferiors. The simile of the beloved person in the position of king and the approach to oppose against her has a more conscious schema in Sa’di’s lyric poems compared to those of other poets. Sa’dibelieves in accepting the obstacle. By this technique, he projects the peace-seeking of the public against the quarreling of the dominant class. Criticism against the power within the framework of love provides this possibility untilSa’di proposes his critical view directly.